Making Copyright Work for the Asian Pacific: Juxtaposing Harmonisation with Flexibility - Lai, Jessica (ANU Press, 2018)
This book provides a contemporary overview of developing areas of copyright law in the Asian Pacific region. While noting the tendency towards harmonisation through free trade agreements, the book takes the perspective that there is a significant amount of potential for the nations of the Asian Pacific region to work together, find common ground and shift international bargaining power. Moreover, in so doing, the region can tailor any regional agreements to suit local needs. The book addresses the development of norms in the region and the ways in which this can occur in light of the specific nature of the creator–owner–user paradigm in the region and the common interests of Indigenous peoples.